Perancangan Batik Papua Motif Asei dengan Pattern Komputer Grafis - Saputro, Agung Dwi; Kuddi, Bobi Frans (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Papua is a province with a diverse culture ranging in language, customs, and traditions. Khombouw is a tradition of carving on bark with various motifs, ranging from motifs of snakes (ehakkai), lizards (fendei), lizards (varaan), fish (ka), eels (Khahlio), cranes (Wandu Khoko), bats ( Pjeakea), flying squirrel (hobahe), leaves (Ovea-havea), forest flower (khamblau, haturi), circular motif (fouw), plot motif (ebew), and genemo leaf motif (ebun). With so many motifs, it would be a shame if they were not explored further because Asei's motifs would only be known among certain circles. The digitization of the asei motif design can be implemented by making it into a batik motif with the application of a computer graphic pattern. To digitize the Asei motif, the method used is a qualitative method which emphasizes the observation of phenomena and more research into the substance to be able to deeply identify the object under study related to digitization in the development of the Asei Sentani motif by using three stages, namely exploration, design, and realization. results. The results of this study are batik cloth motifs that can be used as clothes, hats or tablecloths. With the application of a computer graphic pattern, the asei motif can be implemented into a batik cloth motif that has a selling value